2015
DOI: 10.1002/art.39162
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Associations of Osteoarthritis‐Mediated Loss of Epigenetic Control in Articular Cartilage

Abstract: Objective. To identify osteoarthritis (OA) progressionmodulating pathways in articular cartilage and their respective regulatory epigenetic and genetic determinants in end-stage disease.Methods. Transcriptional activity of CpG was assessed using gene expression data and DNA methylation data for preserved and lesional articular cartilage samples. Disease-responsive transcriptionally active CpG were identified by means of differential methylation between preserved and lesional cartilage. Transcriptionally releva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 42 publications
2
53
0
Order By: Relevance
“…Array-based surveys have revealed significant differences in DNA methylation between OA and non-OA bone and cartilage in the human hip and knee at hundreds to thousands of CpG sites throughout the genome [1116]. In some of these studies, differences among sample groups were most pronounced in genes involved in inflammation and immune-responses [12, 14], while others reported an over-representation of genes involved in developmental pathways [15, 16].…”
Section: Introductionmentioning
confidence: 99%
“…Array-based surveys have revealed significant differences in DNA methylation between OA and non-OA bone and cartilage in the human hip and knee at hundreds to thousands of CpG sites throughout the genome [1116]. In some of these studies, differences among sample groups were most pronounced in genes involved in inflammation and immune-responses [12, 14], while others reported an over-representation of genes involved in developmental pathways [15, 16].…”
Section: Introductionmentioning
confidence: 99%
“…OA is the most prevalent joint condition and a leading cause of disability in the world [2]. In the last years, major efforts have been made to identify genetic and epigenetic mechanisms involved in the development of OA [3] as well as the role of ageing, obesity, joint injury, biomechanical stress, inflammation, hormone levels, metabolic disease, etc. [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The advent of high-throughput CpG DNA methylation arrays has enabled investigators to directly compare, at a genome-wide level, OA and non-OA methylomes and to compare methylation status between DNA from different sites within the joint and between different joints (17)(18)(19)(20)(21)(22). These arrays have also been used to assess whether there are direct links between OA genetic risk loci and epigenetic status, and between gene expression and epigenetics (23,24).…”
Section: Epigenetics and Oamentioning
confidence: 99%
“…Together, these studies demonstrated OA risk alleles that confer susceptibility to OA via changing the epigenetically modulated gene expression. Nonetheless, genomewide analysis of the transcriptome and methylome of articular cartilage revealed that only 24% of the differentially methylated CpG sites correlated to proximal in cis gene expression and as such could be considered transcriptionally active in articular cartilage (19,24). Moreover, it was shown that for 31 and 26 OA cartilage-relevant genes, methylation and expression, respectively, are additionally affected by genetic variation proximal to these genes, which may further modify the OA pathophysiology (19,24).…”
Section: Candidate Gene Analysis Of Dna Methylation In Oamentioning
confidence: 99%